Clinical characteristics, risk factors and outcomes of South-East Asian patients with acute pulmonary embolism. (15th December 2017) - Mok, Kwang How; Wong, Shiun Woei; Wong, Yee May; Foo, David; Watson, Timothy James; Ho, Hee Hwa
Abstract: Background: The clinical features of acute PE have not been well studied in South-East Asia. We therefore sought to evaluate the clinical characteristics, risk factors and outcomes of patients diagnosed with acute pulmonary embolism (PE) in our region. Methods: From January 2008 to March 2013, 343 patients were admitted to our tertiary institution with acute PE. Data were collected retrospectively on baseline clinical characteristics, presenting signs and symptoms, results of electrocardiographic and imaging studies, therapeutic modality and hospital course. Results: 91% of the patients presented with submassive PE. 6.1% of patients had saddle PE. The most common presenting symptom was dyspnea (72.3%) followed by chest pain (12.8%), hemoptysis (2.6%), syncope (2.6%) and cardiovascular collapse (1.2%). Risk factors for PE were idiopathic cause (33.5%), immobilization (21%), malignancy (6.1%) and hypercoagulable state (2.9%). The overall in-hospital mortality was 5%. Factors associated with mortality were massive PE, tachycardia at presentation, right ventricular dysfunction and cardiogenic shock. Bleeding complications occurred in 10.2% of patients (major bleeding in 3.5%). Conclusion: Acute PE in the South-East Asian patients is associated with an overall mortality rate of 5%. The bleeding complications from treatment are also high.